Chanting Down the New Jerusalem Calypso, Christianity, and Capitalism in the Caribbean. - Guadeloupe, Francio (Berkeley : University of California Press, 2008)
In this brilliantly evocative ethnography, Francio Guadeloupe probes the ethos and attitude created by radio disc jockeys on the binational Caribbean island of Saint Martin/Sint Maarten. Examining the intersection of Christianity, calypso, and capitalism, Guadeloupe shows how a multiethnic and multireligious island nation, where livelihoods depend on tourism, has managed to encourage all social classes to transcend their ethnic and religious differences. In his pathbreaking analysis, Guadeloupe credits the island DJs, whose formulations of Christian faith, musical creativity, and capitalist su.
Bc; d; e; f; g; h; i; j; k; l; m; n; o; p; r; s; t; u; v; w; x; y; z.
Description based on print version record.
Keywords: Anthropology of religion -- Saint Martin (West Indies); Disc jockeys -- Social aspects -- Saint Martin (West Indies); Ethnicity -- Saint Martin (West Indies); Ethnology -- Saint Martin (West Indies); Music -- Social aspects -- Saint Martin (West Indies); Religion and culture -- Saint Martin (West Indies); Saint Martin (West Indies) -- Ethnic relations; Saint Martin (West Indies) -- Race relations; Saint Martin (West Indies) -- Social conditions; Social Science; Ethnology -- Saint Martin (West Indies); Ethnicity -- Saint Martin (West Indies); Anthropology of religion -- Saint Martin (West Indies); Religion and culture -- Saint Martin (West Indies); Disc jockeys -- Social aspects -- Saint Martin (West Indies); Music -- Social aspects -- Saint Martin (West Indies); Saint Martin (West Indies) -- Ethnic relations; Saint Martin (West Indies) -- Race relations; Saint Martin (West Indies) -- Social conditions; SOCIAL SCIENCE / Anthropology / Cultural; SOCIAL SCIENCE / Discrimination & Race Relations; SOCIAL SCIENCE / Ethnic Studies / General; SOCIAL SCIENCE / Minority Studies; Electronic books